THE IMPLEMENTATION OF REWARDS AND PUNISHMENTS FOR MOTIVATING STUDENTS IN ENGLISH LEARNING AT TENTH GRADE OF MAN 2 KOTA PROBOLINGGO - Kamilia, Jamilatul; As’ari, As’ari (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
This study aims to find out the kinds of rewards and punishments which motivate students in English learning and, to find out how the implementation of rewards and punishments motivates students in English learning at Tenth grade of MAN 2 Kota Probolinggo. The research was a qualitative research. The researcher collected data from interview and observation. Observation were carried out in one classes, to strengthen research answers or as a supporting method. Interview was conducted with two English teachers to identify the research question in this research. The results from observation and interview showed several rewards used by teachers in the classroom; applause, praise, positif feedback, score, and giving gifts. While, there are some punishments used by teachers; warning, advice and give direction, deducting grades, memorizing vocabulary, standing in front of the class, and sitting squatting on a chair. It was also found that reward and punishment were applied to each class. When the teacher used reward and punishment, the teacher first observed the condition of the students and the atmosphere of the class. Students who get rewards were active, enthusiastic, fast, and correct in answering questions. On the other hand, students who get punished are unfocused, noisy, and undisciplined. AbstrakPenelitian ini bertujuan untuk mengetahui jenis penghargaan dan hukuman yang memotivasi siswa dalam pembelajaran bahasa Inggris dan, untuk mengetahui bagaimana penerapan penghargaan dan hukuman memotivasi siswa dalam pembelajaran bahasa Inggris di kelas sepuluh MAN 2 Kota Probolinggo. Penelitian ini merupakan penelitian kualitatif. Peneliti mengumpulkan data melalui wawancara dan observasi. Observasi dilakukan dalam satu kelas, untuk memperkuat jawaban penelitian atau sebagai metode pendukung. Wawancara dilakukan dengan dua orang guru bahasa Inggris untuk mengidentifikasi pertanyaan penelitian dalam penelitian ini. Hasil observasi dan wawancara menunjukkan beberapa reward yang digunakan guru di kelas; tepuk tangan, pujian, umpan balik positif, skor, dan pemberian hadiah. Sementara itu, ada beberapa hukuman yang digunakan oleh guru; peringatan, nasihat dan pengarahan, pengurangan nilai, menghafal kosa kata, berdiri di depan kelas, dan duduk jongkok di kursi. Ditemukan juga bahwa reward dan punishment diterapkan pada setiap kelas. Pada saat guru menggunakan reward dan punishment, guru terlebih dahulu mengamati keadaan siswa dan suasana kelas. Siswa yang mendapat reward aktif, antusias, cepat, dan benar dalam menjawab pertanyaan. Sebaliknya siswa yang mendapat hukuman adalah siswa yang tidak fokus, ribut, dan tidak disiplin.